Prehospital emergency care patient satisfaction scale [PECPSS] for care provided by emergency medical teams: Scale development and validation - Junpei Haruna; Nobuyasu Hayasaka; Yukiko Taguchi; Saori Muranaka; Sachi Niiyama; Hirotoshi Inamura; Shuji Uemura; Keigo Sawamoto; Hirotoshi Mizuno; Nobuaki Himuro; Eichi Narimatsu (AIMS Press, 2023)
The purpose of this study was to develop and validate an emergency medical technician (EMT) care patient satisfaction scale to measure patient satisfaction with prehospital emergency care. To date, patient satisfaction surveys of EMTs have been performed subjectively, e using each facility's questionnaire, without the use of a validated patient satisfaction scale. However, no specific scale has been devised to assess patient satisfaction with EMTs. The study population comprised patients who used an ambulance between November 2020 and May 2021 (N = 202). A survey instrument was administered to participants who provided informed consent. In the process of validating the patient satisfaction scale, an exploratory factor analysis (EFA) of construct validity was performed. The results of the EFA showed a factor structure consisting of five factors: "teamwork", "explanation and communication", "physical treatment and psychological support", "quickness of transport", and "environment in the ambulance". In addition, domain and summary scores showed good internal reliability (Cronbach's range = 0.82-0.94). The patient satisfaction scale developed in this study was designed and validated considering the role of EMTs and patients' needs for prehospital care. This scale may be useful in the development of assessments and interventions to improve patient satisfaction with EMTs.